Towards efficient synthesis of sugar alcohols from mono- and poly-saccharides: role of metals, supports & promoters - Tathod, Anup P.; Dhepe, Paresh Laxmikant (Green Chemistry, 2014)
{Biomass derived sugar alcohols (xylitol, arabitol) find numerous uses in the food, oral hygiene and pharmaceutical industries. Their direct synthesis from poly-saccharides, however, still remains an immense challenge. In this study, we demonstrate in detail the effects of metals, supports and promoters in enhancing the yields of sugar alcohols from mono- and poly-saccharides. We undertook synthesis of bimetallic catalysts, M-M'/S (M